EDUKASI PENGELOLAAN E-ARSIP DAN MANFAAT ARSIP DIGITAL DI SMK NEGERI 3 DEPOK - Ummy Gusti Salamah; Desti Destiansari Istinabiyah; Ayu Soraya; Soim, Kamilia Syahputra; Feri Nugroho; Nur Fitri Dewi; Risma Ekawati (Politeknik Negeri Sriwijaya, 2024)
The rapid advancement of digital technology has significantly influenced various aspects of daily life. One emerging trend is the use of Digital Archive Applications, commonly referred to as E-Archives. Within the Department of Office Automation and Management at SMK Negeri 3 Depok, students have been introduced to digital archiving practices; however, their experience has primarily been limited to using Google Drive as the main tool for storing digital files. This community service initiative was designed to provide education on digital archive management, highlighting the benefits and advantages of electronic archives compared to conventional manual systems. More importantly, the program aimed to enhance students’ understanding by introducing and demonstrating an E-Archive application developed by the community service team. Through this approach, students at SMK Negeri 3 Depok were expected to gain hands-on experience in managing data using the E-Archive system. The implementation of the activity involved presentations and live demonstrations of the E-Archive application. To reinforce learning outcomes, interactive sessions such as Q&A discussions and quizzes were conducted, enabling students to actively engage and broaden their knowledge of digital archiving.